Telaah ‘Childhood Place Attachment’ sebagai Dasar Perubahan Ruang pada Kompleks Perumahan Modern (studi kasus pada Perumahan Chandra Kirana Regency Singosari) - Widiana, Fenny; Yusran, Yusfan Adeputera (Departemen Arsitektur Fakultas Teknik Universitas Brawijaya, Indonesia, 2017)
Changes in residential units are common happen in a housing complex. Found many houses that are not in accordance with the original house form which planned by the developer in a new housing complex in the district of Malang. It shows that dissatisfaction of residents to the house's design makes them add some changes, especially in the space. This study aims to identify and analyze the attachment of places during childhood and local wisdom that affects the change of space in a housing complex by taking the case in the Chandra Kirana Regency Singosari, Malang. This study uses the qualitative method with phenomenology approach through in-depth interview and field survey on purposive samples, then the result is analyzed with two main elements of local wisdom, that is the man and its nature. From the results of the study found that there is an attachment between childhood memories with the present form of the houses seen from the composition of spatial arrangement in the house. In addition, local wisdom also influences the change.Â